Decreased Intrathecal Concentrations of Free Light Chains Kappa in Multiple Sclerosis Patients Taking Very High Effective Disease-Modifying Treatment - Marie Süße; Franz Felix Konen; Philipp Schwenkenbecher; Kathrin Budde; Matthias Nauck; Matthias Grothe; Malte Johannes Hannich; Thomas Skripuletz (Diagnostics, 2022)
Free light chains kappa (FLCκ) in cerebrospinal fluid (CSF) are a part of the intrathecal immune response. This observational study was conducted to investigate the effects of different disease-modifying therapies (DMT) on the humoral intrathecal immune response in the CSF of patients with multiple sclerosis (MS). FLCκ were analyzed in CSF and serum samples from MS patients taking DMT (n = 60) and those in a control cohort of treatment-naïve MS patients (n = 90). DMT was classified as moderately effective (including INFß-1a, INFß-1b, glatiramer acetate, dimethyl fumarate, teriflunomide, triamcinolone); highly effective (including fingolimod, daclizumab) and very highly effective (alemtuzumab, natalizumab, rituximab/ocrelizumab, mitoxantrone). FLCκ were measured using a nephelometric FLCκ kit. Intrathecal FLCκ and IgG concentrations were assessed in relation to the hyperbolic reference range in quotient diagrams. Intrathecal FLCκ concentrations and IgG concentrations were significantly lower in samples from the cohort of MS patients taking very highly effective DMT than in samples from the cohort of MS patients taking highly effective DMT and in the treatment-naïve cohort (FLCκ: p = 0.004, p < 0.0001 respectively/IgG: p = 0.013; p = 0.021). The reduction in FLCκ could contribute to an anti-inflammatory effect in the CNS through this mechanism. There was no difference in the appearance of CSF-specific oligoclonal bands (p = 0.830). Longitudinal analyses are required to confirm these results.